Hydronephrosis-Induced Polycythemia with Low Erythropoietin Level: A Case Report and Literature Review - Chia-Cheng Chang; Jiann-Shiuh Chen; Chao-Ching Huang; Yuan-Ning Yang; Chih-Chia Chen (Children)
Introduction: Polycythemia is a rare condition that can be either primary or secondary. We report a case of an adolescent with progressive hydronephrosis-induced polycythemia and low erythropoietin levels, along with a thorough literature review. Report of a Case: A 17-year-old girl with epilepsy had progressively elevated hemoglobin levels and low erythropoietin levels. Initial investigations, including genetic surveys and bone marrow studies, showed no evidence of polycythemia vera or myeloproliferative disorders. Further imaging studies revealed severe hydronephrosis on the left side caused by ureteropelvic junction stenosis. Following nephroureterectomy, her hemoglobin levels gradually returned to normal. Conclusions: This case highlights the potential association between hydronephrosis and polycythemia, even with low erythropoietin levels. Renal abnormalities should be considered in the differential diagnosis of pediatric patients with polycythemia, even in the absence of elevation of erythropoietin. Further research is needed to clarify this association and its pathophysiology.